Sex Ratio and Size of First Mature Gonads of Lompa Fish (Thryssa baelama, Forsskal 1773) in the Learisa Kayeli River, Haruku Island - Fadhli Latuconsina; Sharifuddin Bin Andy Omar (BIOSAINSTEK, 2025)
This study aimed to analyze the sex ratio and determine the size at first gonad maturity of Lompa fish (Thryssa baelama) caught in the Learisa Kayeli River, Haruku Island, from May 2019 to April 2020. Samples were collected from two stations using purposive sampling and cast nets. Sex identification and gonad maturity staging were conducted macroscopically in the laboratory. The sex ratio was analyzed using the chi-square test (α = 0.05), while the size at first gonad maturity was estimated using the Spearman-Karber method. A total of 1,090 fish were collected during the study. The overall sex ratio of males to females was 1.11:1.00, with no significant deviation from the expected 1:1 ratio (Station I: χ² = 7.80; Station II: χ² = 18.40; χ² critical = 19.68; df = 11). The mean size at first gonad maturity for males was 101.37 mm at Station I and 106.20 mm at Station II, while for females it was 108.09 mm and 109.02 mm, respectively. These results indicate that male T. baelama reach gonad maturity at smaller sizes than females. The findings provide valuable biological reference data to support local fishery management practices, particularly in regulating the timing of the traditional sasi harvest and recommending appropriate mesh sizes to ensure sustainable utilization of the population.